The Influence of Price and Quality on The Purchase of Honda Scoopy Motorcycle in Banda Aceh City - Hamdani; Ismail (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Currently, Banda Aceh city has a large number of different brands of motorcycles, and new motorcycle products with different advantages and different prices are emerging. This influences consumer purchasing decisions. This fact is also recognized by motorcycle manufacturers, so that every new motorcycle product launch will constantly improve the quality, price and product design demanded by consumers, allowing these products to compete in the market. The purpose of this study was to determine the impact of price and quality on the purchase of Honda He scoopy vehicles in Banda Aceh city. The sample for this study included his 52 respondents, representing 25% of the average population: his 207 Honda and his Scoopy cars sold in his one year. This amount is more than sufficient compared to the minimum number of samples taken (10-25%). (Arrikunt, 2005) Based on the results of multiple regression analysis, all the variables studied, i.e. price and quality factors, have close correlation coefficients (relationships) and strongly influence Honda's purchasing decisions. It turns out. Scoopy vehicle in Banda Aceh